(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
The Correspondence of Ohrid archbishop Theophylact is very precious source for Macedonian History from the end ofXth-beginning of Х1Ѓ Century. Two of his numerous Letters, denoted as L8 (dated in the Second Half / The End of the 1091) and LI3a, written in the First Half of the 1092, contain significant information about Polog’’s administrative, socio-economic and church History at the end of Xfh Century.